Mechanical–Structural Investigation of Chemical Strengthening Aluminosilicate Glass through Introducing Phosphorus Pentoxide - Zeng, Huidan; Wang, Ling; Ye, Feng; Yang, Bin; Chen, Jianding; Chen, Guorong; Sun, Luyi (Frontiers in Materials, 2016)
Chemical strengthening of aluminosilicate glasses through K+-Na+ ion exchange has attracted tremendous attentions because of the accelerating demand for high strength and damage resistance glasses. However, a paramount challenge still exists to fabricate glasses with a higher strength and greater depth of ion-exchange layer. Herein, aluminosilicate glasses with different contents of P2O5 were prepared and the influence of P2O5 on the increased compressive stress and depth of ion-exchange layer was investigated by micro-Raman technique. It was noticed that the hardness, compressive stress, as well as the depth of ion-exchange layer substantially increased with an increasing concentration of P2O5 varied from 1 to 7 mol%. The obtained micro-Raman spectra confirmed the formation of relatively depolymerized silicate anions that accelerated the ion exchange. Phosphorus containing aluminosilicate glasses with a lower polymerization degree exhibited a higher strength and deeper depth of ion-exchange layer, which suggests that the phosphorus containing aluminosilicate glasses have promising applications in flat panel displays, windshields, and wafer sealing substrates.